2020
DOI: 10.1186/s13613-020-00706-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of COVID-19 in Wuhan, China: a large cohort study

Abstract: Background: Since December 2019, an outbreak of Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) initially emerged in Wuhan, China, and has spread worldwide now. Clinical features of patients with COVID-19 have been described. However, risk factors leading to in-hospital deterioration and poor prognosis in COVID-19 patients with severe disease have not been well identified. Methods: In this retrospective, single-center cohort study, 1190 adult inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 35 publications
8
101
1
6
Order By: Relevance
“…1 . Among the included studies, 50 studies were conducted in China [ 6 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ], 27 in the United States [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsunclassified
“…1 . Among the included studies, 50 studies were conducted in China [ 6 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ], 27 in the United States [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsunclassified
“…Notably, we found that the mortality rate was much higher among diabetic patients than in those without (20.0% vs. 4.8%). Other authors have also reported higher rates of comorbid conditions such as cardiovascular, respiratory illnesses, chronic kidney diseases, malignancies, and diabetes mellitus in hospitalized COVID-19 patients [20][21][22][23], and diabetes was found to account for most of these comorbid conditions [24]. Moreover, the presence of diabetes in COVID-19 patients has been consistently reported to increase disease severity and the mortality risk [25,26].…”
Section: Discussionmentioning
confidence: 96%
“…Several biomarkers of COVID-19 have been associated with the disease severity and progression. COVID-19-associated coagulopathy was found more frequent in fatal COVID-19 cases, and a high D-dimer level has been associated with poor prognosis and in-hospital mortality (4)(5)(6). The hypothesis of the presence of microthrombi in lungs and kidneys was suggested after autopsy case series (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%